Geospatial API Architecture with Laravel for Agricultural Land Suitability Detection System - Susetyo, Yerymia Alfa (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
Identification of agricultural land suitability involves a variety of variables that are heterogeneous. The heterogeneity of spatially-based climate and physiographic data is in fact quite complex to solve. Therefore, a spatial-based system architecture that meets the criteria of inclusiveness, collaboration, capacity development, and quick request-response is needed. The research aims to build an API geospatial architecture with Laravel for Agricultural Land Suitability Detection Systems. The geospatial API architecture in this study was built using RESTFul Web services on the Laravel Framework. Simulation architecture involves five nodes as a server and one node as a client. Six main API were produced in this study. Four services are derived from four severs, where services are services related to spatial data (area, altitude, slope, and rainfall). Meanwhile, two other services, relating to conventional information zoning of agricultural land suitability generated by Server 5. The service generated by the last server was successfully implemented on the client-based web-based interactive map application.